Madelung's deformity: capitate-related versus ulna-related measurement methods. (June 2019) - Hegazy, Galal; Mansour, Tarek; Alshal, Ehab; Abdelaziz, Mohammed; Alnahas, Mohammed; El-Sebaey, Ibrahem
Several investigators have defined measurements for Madelung's deformity based on the distal radius or on the longitudinal ulnar axis to avoid the distorted distal radius and its lunate fossa. However, errors may occur in severe cases because of ulnar deformity and displacement. We quantified seven established measurements for Madelung's deformity relying on the central axis of the capitate. The inter- and intrarater reliability of the capitate-related and the ulna-related techniques were compared. We observed a higher inter- and intrarater reliability for the capitate-related method than for the ulna-related method. Better agreement was also observed for measurements of distance than for measurements of angles. However, the palmar tilt angle measurement method was neither reliable nor reproducible. The capitate-related technique can help to accurately determine the severity of Madelung's deformity, assist in surgical planning and identify the prognosis. Level of evidence: III